The Development of Fear Learning and Generalization in 8 to 13 year-olds - Glenn, Catherine R. (2011)
The current study examined developmental changes in fear learning and generalization in 40 healthy 8–13 year-olds using an aversive conditioning paradigm adapted from Lau and colleagues (2008). In this task, the conditioned stimuli (CS+/CS−) are two neutral female faces, and the unconditioned stimulus is a fearful, screaming face. The second phase of the study also included a generalization stimulus (GS): a 50% blend of the CS+/− faces. The eye-blink startle reflex was utilized to measure defensive responding. Patterns of fear learning and generalization were qualified by child age. Older children demonstrated greater fear learning (i.e., larger startle during CS+ than CS−) than younger children. In addition, older children exhibited the typical pattern of generalization observed in adults, whereas younger children did not. Finally, fear learning also related to contingency awareness; only children who correctly identified the CS+ demonstrated fear-potentiated startle to the CS+. Clinical implications and future directions are discussed.